2018
DOI: 10.1039/c7ra10104j
|View full text |Cite
|
Sign up to set email alerts
|

Size effect of oxygen reduction reaction on nitrogen-doped graphene quantum dots

Abstract: The adsorption strength of ORR intermediates, the reaction free energy of rate-determining step, and the overpotential increase with the increase of the size of N-doped graphene quantum dots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…The Koutecky–Levich (K–L) plots of this catalyst showed that the ORR electron‐transfer number ( n ) was 3.82, comparable to that of commercial Pt/C: 3.96. Zhang et al 169 used density functional theory (DFT) to study the effect of the size of N‐GQD on catalytic ORR performance in terms of the adsorption strength of ORR intermediates, reaction free energy, rate‐determining step, and overpotential. The results indicated that the smallest N‐doped GQDs had the smallest overpotential and the highest ORR catalytic activity.…”
Section: Applications Of Cds In Electrocatalysismentioning
confidence: 99%
“…The Koutecky–Levich (K–L) plots of this catalyst showed that the ORR electron‐transfer number ( n ) was 3.82, comparable to that of commercial Pt/C: 3.96. Zhang et al 169 used density functional theory (DFT) to study the effect of the size of N‐GQD on catalytic ORR performance in terms of the adsorption strength of ORR intermediates, reaction free energy, rate‐determining step, and overpotential. The results indicated that the smallest N‐doped GQDs had the smallest overpotential and the highest ORR catalytic activity.…”
Section: Applications Of Cds In Electrocatalysismentioning
confidence: 99%
“…The functionalization procedures of CQD play a fundamental role not only in the PL modulation, but also in many other applications including ORR catalysis [26][27][28], selective oxidation of organic molecules [29], doping of semiconducting membranes [30], drug delivery [19,23], chemical or biosensing [4,31] etc. The functionalization can lead to bulk doping or to definite defect organizations, such as surface passivation by noncovalent bonds or by covalent linkages of different molecules in edge sites.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was shown that O 2 is stabilized significantly when water effects are modeled [10]. Different other aspects such as: the type of doping nitrogen (graphitic, pyridinic, pyrrolic) [7,11,12], concentration of N dopants [9,13,14], solvation effects of reaction intermediates [10,13,15], the size and shape of graphene sheets were investigated to get insights into activities of these materials [16,17]. Even though in recent years N doped graphitic materials (nanotubes, grapheme, etc.)…”
Section: Introductionmentioning
confidence: 99%